2004
DOI: 10.1007/s00105-004-0728-1
|View full text |Cite
|
Sign up to set email alerts
|

Erfolgreiche Therapie einer Haut- und Lungensarkoidose mit Fumars�ureestern

Abstract: A 61-year old female patient with cutaneous sarcoidosis was treated with fumaric acid esters (Fumaderm). After 12 months of therapy, lesions were markedly improved and treatment was discontinued. 18 months later, the cutaneous lesions recurred, angiotensin converting enzyme (ACE) serum levels were increased and a chest X-ray demonstrated pulmonary involvement. Therapy with fumaric acid esters was again started. The skin showed improvement after 2 months and completely cleared within 17 months, within 4 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Treatment with FAEs has been reported to be effective in small case series and case reports of patients with sarcoidosis [5,6,11,12,13,14], while marked to complete remission of skin and pulmonary lesions has been reported (table 1). Dümmler et al [11] presented 2 patients with cutaneous sarcoidosis treated with FAEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with FAEs has been reported to be effective in small case series and case reports of patients with sarcoidosis [5,6,11,12,13,14], while marked to complete remission of skin and pulmonary lesions has been reported (table 1). Dümmler et al [11] presented 2 patients with cutaneous sarcoidosis treated with FAEs.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects included flush, minor gastrointestinal complaints and lymphopenia. Gutzmer et al [13] demonstrated a 61-year-old female patient with cutaneous sarcoidosis treated with FAEs. After 12 months of therapy, lesions were markedly improved and treatment was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action of fumaric acid esters would appear to offer a potential for treatment in this immunological setting. The literature contains reports of sarcoidosis patients with cutaneous as well as systematic disease who have been treated with fumaric acid esters (Table 2) [35, 45]. Treatment was successful not only in cutaneous disease but also with a large portion of patients with systemic disease.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Den Erkenntnissen über die zentrale Rolle der Th1-typischen Zytokine Rechnung tragend, wurde bereits auch über erfolgreiche Behandlungen mit topischen Immunmodulatoren wie Tacrolimus und systemischen Therapien mit Ciclosporin A und sogar TNF-α-Inhibitoren wie Adalimumab oder Infliximab berichtet. Diese "off-label" eingesetzten Mittel sollten dann in Erwägung gezogen werden, wenn andere Therapien versagen [3,4,5,6].…”
Section: Diskussionunclassified